1981
DOI: 10.1177/014662168100500405
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Equity in Intimate Relations

Abstract: It has been suggested that equity theory, a social psychological theory concerned with the fairness in casual relationships, should be applicable to inti mate relations as well. As a first step in that direc tion, this report describes the development of the Traupmann-Utne-Walster Equity/Inequity Scales, which measure the level of equity that intimate couples perceive in their relationships. The scales, which include items from four areas of concern for intimates—personal concerns, emotional concerns, day-to-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…In general, both underbenefiting and overbenefiting in relationships have been found to be related to a lack of satisfaction or well-being, and underbenefiting was related more closely to distressing emotions than was overbenefiting (Sprecher 1986;Traupmann, Petersen, Utne, and Hatfield 1981). It is difficult to interpret the results of our study on reciprocity at the network level.…”
Section: Discussionmentioning
confidence: 54%
“…In general, both underbenefiting and overbenefiting in relationships have been found to be related to a lack of satisfaction or well-being, and underbenefiting was related more closely to distressing emotions than was overbenefiting (Sprecher 1986;Traupmann, Petersen, Utne, and Hatfield 1981). It is difficult to interpret the results of our study on reciprocity at the network level.…”
Section: Discussionmentioning
confidence: 54%
“…This measure taps into perceptions of relational equity, based only on one individual's response. The HGEM has strong test-retest reliability, as well as good construct and face validity (Sprecher, 2001), and it is a widely used measure of global equity (Stafford & Canary, 2006;Young & Hatfield, 2011); moreover, in spite of its simplicity, it is seen as one of the most valid ways to assess global equity (Traupmann, Peterson, Utne, & Hatfield, 1981). There exists disagreement in literature about the proper analytic use of the HGEM, with some researchers categorizing the variables by recoding all of the items that are positive as "overbenefited," all the negative items as "underbenefited," and the zero point as "equitable" to represent three categories.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its brevity, this widely used equity measure has been found to possess reasonable reliability and validity (see Canary & Stafford, 1992;Sprecher, 1986Sprecher, , 1988Traupmann, 1978;Traupmann et al, 1981;VanYperen & Buunk, 1990). In a longer version of the Equity measure, Traupmann, and her colleagues (1981) found that the measure possessed reasonable reliability and validity (Chronbach's for total inputs = .87; for total outputs scales = .90).…”
Section: Methodsmentioning
confidence: 99%